The effect of fatigue on strength-power tests for distinguishing elite-level male kickboxers - Özbay, S.; Gençoglu, C.; Ulupinar, S.; Çinar, V.; Ouergui, I.; Hölbling, D. (Isokinetics and Exercise Science, 2025)
BACKGROUND: Based on recent research, slight performance differences, particularly dependent on the state of recovery, might be crucial for tournament success among elite-caliber kickboxers.